Low‐dose suramin in autism spectrum disorder: a small, phase I/II, randomized clinical trial. Issue 7 (26th May 2017) - Naviaux, Robert K.; Curtis, Brooke; Li, Kefeng; Naviaux, Jane C.; Bright, A. Taylor; Reiner, Gail E.; Westerfield, Marissa; Goh, Suzanne; Alaynick, William A.; Wang, Lin; Capparelli, Edmund V.; Adams, Cynthia; et al.
Abstract: Objective: No drug is yet approved to treat the core symptoms of autism spectrum disorder (ASD). Low‐dose suramin was effective in the maternal immune activation and Fragile X mouse models of ASD. The Suramin Autism Treatment‐1 (SAT‐1) trial was a double‐blind, placebo‐controlled, translational pilot study to examine the safety and activity of low‐dose suramin in children with ASD. Methods: Ten male subjects with ASD, ages 5–14 years, were matched by age, IQ, and autism severity into five pairs, then randomized to receive a single, intravenous infusion of suramin (20 mg/kg) or saline. The primary outcomes were ADOS‐2 comparison scores and Expressive One‐Word Picture Vocabulary Test (EOWPVT). Secondary outcomes were the aberrant behavior checklist, autism treatment evaluation checklist, repetitive behavior questionnaire, and clinical global impression questionnaire. Results: Blood levels of suramin were 12 ± 1.5 μ mol/L (mean ± SD) at 2 days and 1.5 ± 0.5 μ mol/L after 6 weeks. The terminal half‐life was 14.7 ± 0.7 days. A self‐limited, asymptomatic rash was seen, but there were no serious adverse events. ADOS‐2 comparison scores improved by −1.6 ± 0.55 points ( n = 5; 95% CI = −2.3 to −0.9; Cohen's d = 2.9; P = 0.0028) in the suramin group and did not change in the placebo group. EOWPVT scores did not change. Secondary outcomes also showed improvements in language, social interaction, and decreased restricted or repetitive behaviors. Interpretation: The safety and activity of low‐dose suramin showed promise as a novel approach to treatment of ASD in this small study.